2014
DOI: 10.1177/1091581814555915
|View full text |Cite
|
Sign up to set email alerts
|

Toxicodynamic and Toxicokinetic Descriptors of Combined Chromium (VI) and Nickel Toxicity

Abstract: After repeated intraperitoneal injections of nickel and chromium (VI) salts to rats, we found, and confirmed by mathematical modeling, that their combined subchronic toxicity can either be of additive type or depart from it (predominantly toward subadditivity) depending on the effect assessed. Against the background of moderate systemic toxicity, the combination under study proved to possess a marked additive genotoxicity assessed by means of the random amplification of polymorphic DNA test. We also demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…The main inferences from the mathematical modeling of binary toxic combinations briefly postulated in the Introduction have been proved to be virtually identical for different combined toxics Katsnelson et al, 2014;Minigaliyeva et al, 2014;Panov et al, 2015). Taking into consideration that the main purpose of this article is to validate the proposed risk-oriented approach to characterizing three-factorial toxic combinations, we deem it appropriate not to dwell too long on the three two-factorial ones (Ni-Mn.…”
Section: Two-factorial Combined Toxicitymentioning
confidence: 97%
See 1 more Smart Citation
“…The main inferences from the mathematical modeling of binary toxic combinations briefly postulated in the Introduction have been proved to be virtually identical for different combined toxics Katsnelson et al, 2014;Minigaliyeva et al, 2014;Panov et al, 2015). Taking into consideration that the main purpose of this article is to validate the proposed risk-oriented approach to characterizing three-factorial toxic combinations, we deem it appropriate not to dwell too long on the three two-factorial ones (Ni-Mn.…”
Section: Two-factorial Combined Toxicitymentioning
confidence: 97%
“…In a series of papers published by our team during the last two years Katsnelson et al, 2014;Minigaliyeva et al, 2014;Panov et al, 2015), we have discussed the state of the art in the complicated domain of the combined toxicity theory and its mathematical modeling. The mainstream philosophy dominating in the relevant scientific literature as well as in some official guidelines or recommendations and its controversies have been critically overviewed by us, mainly in the first of the abovementioned articles, to which we refer our readers rather than repeating that overview here.…”
Section: Introductionmentioning
confidence: 99%
“…Carcinogenic and mutagenic potential of nickel were also demonstrated [3]. This element is transported by blood and is retained by various tissues or excreted, mainly through urine, making thus the kidney the most target organ of nickel toxicity and carcinogenicity [4]. Studies in the distribution of nickel following acute i. p. injection of nickel in rats showed that the highest accumulation of nickel was in the kidney [5].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, human health effects in epidemiological studies are associated with exposure to mixtures of substances, making determination of the toxicity relationship (e.g., additivity) of nickel substances with each other and with other substances difficult. Recent rat intraperitoneal toxicity studies and mathematical modeling of binary and/or ternary combinations of manganese, chromium (VI) and nickel demonstrated additivity and/or subadditivity of combined subchronic toxicity effects [240,241]; these effects were influenced by dose, effect level, and type of effect assessed. In another study, with oral gavage administration of soluble forms of zinc, copper, manganese, chromium, cadmium, lead, mercury and nickel to rats, systemic toxicity, mortality and effects on neurobehavioral function were observed dose-dependently at the two highest mixture exposure levels of 464 and 1000 mg/kg bw [242].…”
Section: Mixturesmentioning
confidence: 99%